Pengaruh Motivasi Belajar dan Pendapatan Orang Tua Terhadap Minat Mahasiswa Mengikuti Pendidikan Profesi Guru (PPG) - Shaftian Trianwenda; Marwan Marwan; Elvi Rahmi (Universitas Negeri Padang, 2020)
This study aims to investigate the effects of the learning motivation and parents’ incomes on the college student interest in joining the PPG program study at the Department of Economic education FE UNP. This research is associative descriptive. The research variables were the college student interest in joining the PPG program, learning motivation, and parents’ incomes. The research sample comprised college students 2015 and 2016 admission year using the Proportional Random Sampling technique with a total of 130 college students. The data was collected through a questionnaire. Methods of data analysis using multiple regression. The results of the study partially show: (1) there is a significant negative influence between learning motivation and college student interest in joining the PPG program, (2) there is a significant positive effect of parents' income on college student interest. in joining the PPG program, and (3) there is a significant positive effect between learning motivation and parents' income on college students' interest in joining the PPG program. The coefficient of determination (R²) is 0.086. this means that the contribution of independent variables of learning motivation and parent's income to the dependent variable of student interest in joining the PPG program was 8,6%. Keywords: ppg program, learning motivation, parents’ incomes